THE ABILITY OF THE ELEVENTH GRADE STUDENTS OF SMA DELI MURNI BANDAR BARU ON USING COUNTABLE ANDUNCOUNTABLE NOUNS IN THE ACADEMIC YEAR OF 2020/2021 - Karo, Tesalonika Br; Lumbanraja, Viator; Sembiring, Novalina (Kairos English Language Teaching Journal, 2021)
The purpose of this research is to describe the ability of the eleventh-grade students of SMA Deli Murni Bandar Baru on using Countable and Uncountable Nouns. The population of this research was the eleventh-grade students, with 58 students taken as sample. The instrument of collecting data is a test concerning Countable and Uncountable Nouns. The tryout test was done to know the validity, reliability, item difficulty of test items. The result showed that 5 students (15 %) belong to the high category, 24 students (73 %) to the moderate category, and 4 students (12 %) to the low category. The mean score was 61,39 it was only 24 % of the total students who can do the test well with 12 students who get a score above 75, it means that the eleventh-grade students of SMA Deli Murni Bandar Baru are not yet able to use Countable and Uncountable Nouns. Based on the total incorrect answers made by the students in using countable and uncountable was 502. The percentage of studentsâ€™ mistakes made by students in uncountable multiple choice including indefinite and quantifier uncountable was 33 %, in countable multiple choice including singular, regular, irregular countable 34%, in the countable essay including regular and irregular countable was 33%. Based on the findings and conclusions, some suggestions are offered to English teachers, English students, and other researchers. Especially to English teachers, who teach in school, are advised to improve students’ ability to use countable and uncountable nouns.